Mechanical Ventilator VENT19 - Tsuzuki, Marcos S. G. (Polytechnica, 2021)
The SARS-CoV2 virus has spread world wide rapidly. Although a small fraction of the infected people need special care, this number is much greater than what the healthcare systems support. In the most severe cases, mechanical ventilation is crucial for patient recovery, but not available in the needed quantity. In Brazil, mechanical ventilators are mainly imported and at a high cost, increased by the pandemic and the economic crisis, and with high delivery delay, aggravated by the risk of infection of incoming ships, airplanes and external goods. In this sense, an emergency mechanical ventilator developed and produced in the country could save many lives due to the lack of mechanical ventilators. To address this issue, this paper describes the effort to develop such a device.